2019
DOI: 10.1158/1535-7163.targ-19-b011
|View full text |Cite
|
Sign up to set email alerts
|

Abstract B011: Synergistic activity of tazemetostat in combination with androgen signaling inhibitors in preclinical models of prostate cancer demonstrates potential for clinical expansion

Abstract: Prostate cancer (PCa) is the second leading cause of cancer death among men in the United States. Current available treatments include chemical castration and therapies targeting androgen receptor (AR) signaling pathways. Although initial responses are observed, 30% of patients have primary resistance to both forms of treatment and the majority of patients progress from androgen-dependent PCa (ADPC) to castration-resistant PCa (CRPC). Studies on mechanisms of resistance suggest that AR signaling remains a key … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Given the combined roles of AR and EZH2 in driving neuronal gene programs in PCa 36 , we hypothesized that simultaneous inhibition of these molecules with a drug combination could be therapeutic in NEPC. Supporting this, a recent study found that combining the EZH2 inhibitor tazemetostat with the AR inhibitor enzalutamide had beneficial effects in NEPC 39 . To explore the therapeutic potential further, we investigated the effects of combined EZH2 and AR inhibition via exosomes in NEPC models (Fig.…”
Section: Combination Of Tazemetostat and Enzalutamide Delivered Via E...mentioning
confidence: 75%
See 1 more Smart Citation
“…Given the combined roles of AR and EZH2 in driving neuronal gene programs in PCa 36 , we hypothesized that simultaneous inhibition of these molecules with a drug combination could be therapeutic in NEPC. Supporting this, a recent study found that combining the EZH2 inhibitor tazemetostat with the AR inhibitor enzalutamide had beneficial effects in NEPC 39 . To explore the therapeutic potential further, we investigated the effects of combined EZH2 and AR inhibition via exosomes in NEPC models (Fig.…”
Section: Combination Of Tazemetostat and Enzalutamide Delivered Via E...mentioning
confidence: 75%
“…Given the recent findings showing a persistent role of AR in NEPC wherein it plays a concerted role with EZH2 in driving neuronal gene programs in PCa 36 , the combined inhibition of AR and EZH2 by using a combination of EZH2 inhibitor tazemetostat with AR inhibitor enzalutamide has been found to be viable strategy in NEPC 39 . Tazemetostat is a small molecule selective and S-adenosyl methionine competitive inhibitor of histone methyltransferase EZH2 37 with anti-neoplastic activity that is FDA approved for epithelioid sarcoma and follicular lymphoma.…”
Section: Discussionmentioning
confidence: 99%